Clonidine Does Not Reduce Pain or Opioid Consumption After Noncardiac Surgery. (September 2016) - Turan, Alparslan; Babazade, Rovnat; Kurz, Andrea; Devereaux, Phillip J.; Zimmerman, Nicole M.; Hutcherson, Matthew T.; Naylor, Amanda J.; Ali Sakr Esa, Wael; Parlow, Joel; Gilron, Ian; Honar, Hooman; Salmasi, Vafi; et al.
Abstract : BACKGROUND: Clonidine is an α2-adrenoceptor agonist, which has analgesic properties. However, the analgesic efficacy of perioperative clonidine remains unclear. We, therefore, tested the hypothesis that clonidine reduces both pain scores and cumulative opioid consumption during the initial 72 hours after noncardiac surgery. METHODS: Six hundred twenty-four patients undergoing elective noncardiac surgery under general and spinal anesthesia were included in this substudy of the PeriOperative ISchemia Evaluation-2 trial. Patients were randomly assigned to 0.2 mg oral clonidine or placebo 2 to 4 hours before surgery, followed by 0.2 mg/d transdermal clonidine patch or placebo patch, which was maintained until 72 hours after surgery. Postoperative pain scores and opioid consumption were assessed for 72 hours after surgery. RESULTS: Clonidine had no effect on opioid consumption compared with placebo, with an estimated ratio of means of 0.98 (95% confidence interval, 0.70–1.38); P = 0.92. Median (Q1, Q3) opioid consumption was 63 (30, 154) mg morphine equivalents in the clonidine group, which was similar to 60 (30, 128) mg morphine equivalents in the placebo group. Furthermore, there was no significant effect on pain scores, with an estimated difference in means of 0.12 (95% confidence interval, −0.02 to 0.26); 11-point scale; P = 0.10. Mean pain scores per patient were 3.6 ± 1.8 for clonidine patients and 3.6 ± 1.8 for placebo patients. CONCLUSIONS: Clonidine does not reduce opioid consumption or pain scores in patients recovering from noncardiac surgery.